EVALUASI KEBIJAKAN PROGRAM HOME INDUSTRY UNGGULAN DI KOTA PALOPO - Ulfa Ulfa; Dhela Auliya Kusumayani; Rizka Amelia Armin (Hukum Ekonomi Syariah, Fakultas Syariah, IAIN Palopo, 2019)
This study aims to describe the policy evaluation of the Featured Home Industry program in Palopo City by looking at the program policy evaluation indicators, namely technical feasibility, economic and financial opportunities, political support capacity, and organizational carrying capacity. The type of research used is descriptive qualitative research type intended to reveal the problem to be investigated by describing the subject and object of research based on existing facts about the Khilan Industry program. Data obtained through observation, interviews, and documentation of a number of informants. The results showed that initially the khilan program could improve the economic level of the community, but the subsequent development of the achievement of the results was not optimal because of the 50 khilan groups that were previously members of the khilan group, now only 3 groups are still actively producing, selling raw materials for making khilan products in the form of zaro snacks. purchased from the khilan group at low prices, while the manufacturing process takes days, causing bottlenecks in the production of raw materials.